2016
DOI: 10.13189/cor.2016.040403
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Education in Nigeria: Findings from a Community-based Intervention by a Physicians' Association

Abstract: Objectives: Cancer causes significant morbidity and mortality in Nigeria, but the country lacks an organized cancer control system. Low awareness of cancers among health professionals in the country contributes to weak cancer control capabilities and poor patient outcomes in Nigeria. This study describes findings from a community-based education intervention by Medical Women's Association of Nigeria and American Society of Clinical Oncology in Akwa Ibom State. Methods: Intervention was the Cancer Control in Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Low political will has been identified as challenge to adapt the present plan need to further explore the role of health insurance organization and how to mobilize financial resources for sustainable cancer control. Meanwhile, evidence showed that Nigerian health care professionals have limited knowledge about 46,47 cancer care , and the need to improve cancerrelated education among health professionals in 48 Nigeria has been recognized. The national cancer control plan also acknowledged the dearth of adequately-skilled clinicians who provide cancer 12 services.…”
Section: Ghanamentioning
confidence: 99%
“…Low political will has been identified as challenge to adapt the present plan need to further explore the role of health insurance organization and how to mobilize financial resources for sustainable cancer control. Meanwhile, evidence showed that Nigerian health care professionals have limited knowledge about 46,47 cancer care , and the need to improve cancerrelated education among health professionals in 48 Nigeria has been recognized. The national cancer control plan also acknowledged the dearth of adequately-skilled clinicians who provide cancer 12 services.…”
Section: Ghanamentioning
confidence: 99%
“…although breast cancer is the most common malignancy affecting women in Nigerian [5][6] the use of clinical pathways (CPs) for the management of breast cancer is not common practice in Nigerian hospitals [7].…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is the second most common malignancy affecting Nigerian women, and contributes the highest cancer-related mortality in this population [1][2]. Despite this rising prevalence Nigerian healthcare professionals do not have adequate skills and resources in screening, diagnosing, treating and following up women with breast cancer [2][3][4]. The relatively low cancer-related competence is further complicated by the lack of locally-sensitive clinical pathways in most local link evidence to practice for specific health conditions, thereby optimizing patient outcomes and maximize clinical efficiency [5][6].…”
Section: Introductionmentioning
confidence: 99%